2022
DOI: 10.3390/agronomy12092005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Foliar and Soil Boron Fertilization on Yield, Leaf Physiological Traits and Fruit Attributes in Rainfed Almond Orchards

Abstract: Boron (B) fertilizers are recognized as essential for ensuring yield and fruit quality. However, the importance of soil and foliar B fertilization in almond orchards under rainfed conditions is presently unclear. To address this literature gap, in the present study, the impact of soil and foliar application of B on leaf gas exchange, leaf photosynthetic pigments, yield, and fruit quality in almonds was investigated across three consecutive growing seasons. Boron fertilizer was applied to the soil at four rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In addition, high values of carbonates, active limestone, and AB reduced the soil quality in the studied orchards because they can compromise crop development. In fact, a recent study showed that low soil boron contents enhanced almond yield in Portugal [45]. These results suggested that the evaluated soils could be adequate for almond production, but they require management actions to improve their quality to increase the sustainability of these agroecosystems, such as the application of organic amendments, as suggested by Villa et al [46].…”
Section: Discussionmentioning
confidence: 89%
“…In addition, high values of carbonates, active limestone, and AB reduced the soil quality in the studied orchards because they can compromise crop development. In fact, a recent study showed that low soil boron contents enhanced almond yield in Portugal [45]. These results suggested that the evaluated soils could be adequate for almond production, but they require management actions to improve their quality to increase the sustainability of these agroecosystems, such as the application of organic amendments, as suggested by Villa et al [46].…”
Section: Discussionmentioning
confidence: 89%
“…Both B toxicity and deficiency present similar symptoms in plants, including a decrease in photosynthesis, and efficiency of photosystem II, low transpiration rate and stomatal conductance, alterations in the activity of antioxidative enzymes, and increased lipid peroxidation [ 36 , 37 , 38 ]. On the other hand, optimal B supply exerted a positive effect on gas exchange parameters such as the net CO 2 assimilation rate and stomatal conductance in almond ( Prunus dulcis ) [ 39 ]. Similarly, in Zea mays plants, B application considerably improved growth, photosynthetic capacity, tissue B concentration, as well as the antioxidant defense system [ 40 ].…”
Section: Discussionmentioning
confidence: 99%